Systemic to Pulmonary Collaterals in Extremely Low Birth Weight Infants: Incidence, Clinical Significance, and Hemodynamic Features - Hayek, Cynthia; Cayabyab, Rowena; Thompson, Ima; Ebrahimi, Mahmood; Siassi, Bijan; Ramanathan, Rangasamy (American Journal of Perinatology, 2019)
Objective This study aimed to determine the incidence of systemic to pulmonary collaterals (SPCs) in extremely low birth weight infants and to assess its clinical and hemodynamic significance beyond the neonatal period.Study Design Retrospective cohort study was conducted on 61 infants with echocardiogram performed at the time of discharge to determine the presence of SPC and to measure the right and left ventricular outputs and left atrium to aortic ratio. We compared two groups: small or no SPC (Group 1) to moderate or large SPC (Group 2) on demographics, clinical outcomes, and echocardiographic parameters.Results Sixty-one infants were included. The incidence of SPC was 57%; 21% of infants had moderate or large shunts and 31% had small SPC. Demographics, clinical outcomes, and echocardiographic parameters were not significantly different between small or no SPC and moderate to large SPC.Conclusion More than half of the infants had SPC. The size of the shunt did not affect the clinical outcomes nor the echocardiographic parameters measured. All infants had cardiac output above the normative mean.
Keywords: systemic to pulmonary collateral; extremely low birth weight; echocardiogram; very low birth weight; patent ductus arteriosus